Sugars and cuticular waxes impact sugarcane aphid (Melanaphis sacchari) colonization on different developmental stages of sorghum. (May 2023) - Cardona, Juan Betancurt; Grover, Sajjan; Bowman, Michael J.; Busta, Lucas; Kundu, Pritha; Koch, Kyle G.; Sarath, Gautam; Sattler, Scott E.; Louis, Joe
Abstract: Sugarcane aphid (SCA; Melanaphis sacchari ) is a devastating pest of sorghum ( Sorghum bicolor ) that colonizes sorghum plants at different growth stages. Leaf surface characteristics and sugars often influence aphid settling and feeding on host plants. However, how changes in cuticular waxes and sugar levels affect SCA establishment and feeding at different development stages of sorghum have not been explored. In this study, two- and six-week-old BTx623 plants, a reference line of sorghum, was used to evaluate plant-aphid interactions. Monitoring aphid feeding behavior using Electrical Penetration Graph (EPG) technique revealed that aphids spent more time in the sieve element phase of six-week-old plants compared to two-week-old plants. Significant differences were found in the time spent to reach the first sieve element and pathway phases between the two- and six-week-old plants. However, no-choice aphid bioassays displayed that SCA population numbers were higher in two-week-old plants compared to six-week-old plants. Differences in the abundance of wax and sugar contents were analyzed to determine how these plant components influenced aphid feeding and proliferation. Among the cuticular wax compounds analyzed, α-amyrin and isoarborinone increased after 10 days of aphid infestation only in six-week-old plants. Trehalose content was significantly increased by SCA feeding on two- and six-week-old plants. Furthermore, SCA feeding depressed sucrose content and increased levels of glucose and fructose in two-week-old but not in six-week-old plants. Overall, our study indicates that plant age is a determinant for SCA feeding, and subtle changes in triterpenoids and available sugars influence SCA establishment on sorghum plants. Highlights: Sugarcane aphids (SCA) preferred to colonize on two-week-old plants compared to six-week-old sorghum plants. However, SCA fed significantly more from the sieve elements of six-week-old plants compared to two-week-old sorghum plants. SCA feeding enhanced the accumulation of cuticular wax triterpenoids in six-week-old sorghum plants. Trehalose content was significantly increased by SCA feeding on two- and six-week-old sorghum plants.